On achieving gender equity within the liver transplantation medical and surgical workforce - Verran, Deborah (Frontiers in Transplantation, 2024)
Until relatively recently there has been a paucity of readily available information pertaining to the demographics of the medical and surgical workforces for the subspecialty of liver transplantation. This is relevant as it relates to whether gender equity is now being achieved across this particular workforce. This manuscript focuses on what eventually led to the recognition that more comprehensive data were required along with what is now actually known with respect to the gender ratios of the liver transplant workforce along with their related academic activities. Potential solutions to address any ongoing imbalances are also examined. The extent and range of gender disparities previously reported for other cohorts of physicians and surgeons, are also apparent amongst the liver transplant workforce in most regions of the world. This also pertains to the higher leadership positions within liver transplant centers as well as for the related editorial and scientific congress roles. Common themes/recommendations are now emerging as to how best to address the lack of progress towards gender equity. These include the development and implementation of policies, the removal of barriers to career progression, and proper governance. Ongoing actions are going to be required to achieve gender equity across the workforce in liver transplantation around the world.